5G/B5G oriented intelligent cloud network architecture - Xu ZHOU; Zhuo LI; Yifang QIN (Dianxin kexue)
The emergence of 5G/B5G technology has greatly improved the key capabilities of mobile networks including bandwidth,latency and connectivity.Faced with the prosperous development of mobile access side capabilities,the existing centralized architecture for internet cloud service was prone to bottlenecks and could not fully exploit the advantage of 5G/B5G.The technology named Network 5.0 was proposed to address the demand for data networks from future typical network applications through a complete set of innovative protocol systems and control management architecture.A new type of intelligent cloud network based on the protocol system of Network 5.0 was proposed,which could bridge the gap between the internet service model and 5G/B5G access capability through the deep integration of cloud network,and promote further the continuous evolution of the network.